$h^2 + \left( \dfrac{b - a}{2} \right)^2 = a^2$

$h = \sqrt{a^2 - \dfrac{(b - a)^2}{4}}$

$h = \frac{1}{2} \sqrt{4a^2 - (b - a)^2}$

Capacity is maximum if area is maximum:

$A = \frac{1}{2}(b + a)h$

$A = \frac{1}{2}(b + a) \left( \frac{1}{2} \sqrt{4a^2 - (b - a)^2} \right)$

$A = \frac{1}{4}(b + a) \sqrt{4a^2 - (b - a)^2}$ (*take note that 'a' is constant*)

$\dfrac{dA}{db} = \dfrac{1}{4} \left[ (b + a) \dfrac{-2(b - a)}{2\sqrt{4a^2 - (b - a)^2}} + \sqrt{4a^2 - (b - a)^2} \right] = 0$

$\sqrt{4a^2 - (b - a)^2} = \dfrac{b^2 - a^2}{\sqrt{4a^2 - (b - a)^2}}$

$4a^2 - (b - a)^2 = b^2 - a^2$

$4a^2 - b^2 + 2ab - a^2 = b^2 - a^2$

$2b^2 - 2ab - 4a^2 = 0$

$b^2 - ab - 2a^2 = 0$

$(b + a) (b - 2a) = 0$

For b + a = 0; b = -a (meaningless)

For b - 2a = 0; b = 2a (*ok*)

Use b = 2a *answer*